Collaborative Governance Dalam Pengembangan Wisata Romokalisari Adventure Land Surabaya - Maharani Senaen, Windriyani; Siswanto M, Djoko (Institut Riset dan Pengembangan Indonesia, 2024)
The sustainable tourism sector or sustainable tourism is the main focus of the Indonesian government so that the role of Collaborative Governance, namely the involvement of the government, the private sector and the community, is important in efforts to develop sustainable tourism in Indonesia, one of which is the development of coastal tourism at Romokalisari Adventure Land in Surabaya City using the Collaborative Governance concept. (Ratner, 2012) based on library research methods or literature studies, researchers succeeded in finding collaborative synergies that have been implemented by the Surabaya City Government with the main focus of reducing poverty and improving the economy of coastal communities. Third party collaboration gives a new color to tourism in Surabaya, the Metropolitan City has tourism with an adventure land concept involving community empowerment, which is the best achievement of the Surabaya City Government. However, there are still developments that must continue to be pursued in developing the rides and facilities of Romokalisari Adventure Land in order to increase tourist attraction and make Romokalisari Adventure Land a sustainable tourist spot that can be enjoyed in the long term in the city of Surabaya.